The influence of the acquisition of English as a foreign language on acceptability judgements in L1 Polish among young adults. Issue 1 (2nd January 2022) - Pułaczewska, Hanna
ABSTRACT: The article discusses the results of a study of L1 proofreading competence conducted among young adult native speakers of Polish who acquired English through formal education at school and university in Poland. Students with various levels of proficiency in English were asked to make acceptability judgements for Polish structures presented to them in writing. The results confirm the hypothesis that competence in L2 English exerts an influence on judgements of well-formedness of linguistic expressions in L1 Polish. Students with the strongest and weakest language skills in L2 English demonstrated significantly higher competence in detecting non-standard constructions in L1 Polish than students with intermediate L2 proficiency. The largest disparity appeared in the area of lexical semantics. A reinterpretation of the results of a similar study by Sunde and Kristoffersen. [2018. Effects of English L2 on Norwegian L1. Nordic Journal of Linguistics 41, no. 3: 275–307] conducted in Norway is proposed to explain the difference in the findings. The article proposes possible explanations for why strongest cross-lingual influence occurred in students who showed intermediate competence in English, and discusses the potential implications of the findings for language teaching on the one hand, and normative language attitudes on the other.